2019
DOI: 10.26442/00403660.2019.02.000080
|View full text |Cite
|
Sign up to set email alerts
|

Small intestinal diverticula

Abstract: The prevalence of small intestinal diverticula (SID) in the population is 0.5-2.3%, and in most cases they are asymptomatic. In the presence of small intestinal bacterial overgrowth this results in chronic diarrhea and malabsorption. When it is complicated by diverticulitis it causes pain and other symptoms of inflammatory bowel disease. Inflammatory process progression may be accompanied by bleeding, invagination, intestinal obstruction, diverticulum abscess and perforation with peritonitis development. SID i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…In comparison to small bowel diverticulosis, in Western countries, colonic diverticulosis and diverticulitis predominately affect the sigmoid colon [ 1 ]. The prevalence of colonic diverticulosis in the United States by age 60 is 60% [ 1 ], whereas the prevalence of small bowel diverticulosis within the population is 0.5-2.3% [ 8 ]. Both small intestine and colonic diverticula are associated with complications, including diverticulitis, hemorrhage, perforation, abscess formation, and obstruction, although clinical presentation varies, [ 1 , 3 , 4 ], and, as in this case presentation, may mimic other pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison to small bowel diverticulosis, in Western countries, colonic diverticulosis and diverticulitis predominately affect the sigmoid colon [ 1 ]. The prevalence of colonic diverticulosis in the United States by age 60 is 60% [ 1 ], whereas the prevalence of small bowel diverticulosis within the population is 0.5-2.3% [ 8 ]. Both small intestine and colonic diverticula are associated with complications, including diverticulitis, hemorrhage, perforation, abscess formation, and obstruction, although clinical presentation varies, [ 1 , 3 , 4 ], and, as in this case presentation, may mimic other pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, we also found that diseases are often found in living organisms, such as Ascarislumbricoides , suspected Crohn's disease and small intestinal diverticulum[ 22 - 24 ]. Ascarislumbricoides can be cured quickly by the combined application of albendazole and ivermectin[ 25 ].At present, there isno good solution for small intestinal diverticulum and small intestinal tumor[ 26 , 27 ]. In the future, the precise treatment of lesions may be realized through small intestine endoscopes and laparoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…TB itself can present as an intestinal disease mimicking a malnutrition status (19). In fact, intestinal TB may be misdiagnosed as a malabsorption syndrome (20)(21)(22)(23)(24)(25)(26). In one study, 13% and 9% of severely malnourished children were diagnosed with CD and TB respectively (27).…”
Section: Discussionmentioning
confidence: 99%